Pemberdayaan Psikologis dan Iklim Pembelajaran dengan Mediasi Berbagi Pengetahuan tentang Kemampuan Pemasaran Digital di Kalangan UMKM - Prameswari, Puri; Alirejo, M Subroto (Awatara Publisher, 2026)
This study examines how psychological empowerment and learning climate influence digital marketing capability among MSMEs, with knowledge sharing as a mediating variable. Drawing on the Knowledge-Based View, the research conceptualizes digital marketing capability as an outcome of knowledge integration shaped by individual motivation and organizational context. A quantitative survey was conducted among MSMEs engaged in digital marketing activities, and the data were analyzed using PLS-SEM. The results indicate that psychological empowerment has a significant positive effect on digital marketing capability, suggesting that empowered individuals are more proactive in adopting and utilizing digital marketing tools. Learning climate also shows a significant positive relationship with digital marketing capability, highlighting the importance of organizational support for continuous learning. Knowledge sharing exhibits the strongest direct effect on digital marketing capability and significantly mediates the relationships between psychological empowerment and digital marketing capability, as well as between learning climate and digital marketing capability. These findings demonstrate that digital marketing capability is not solely driven by technology adoption but also by internal knowledge processes. The study contributes theoretically by integrating psychological and contextual factors into a knowledge-based explanation of capability formation and offers practical guidance for MSMEs seeking to strengthen their digital marketing performance through empowerment, learning support, and systematic knowledge sharing.